Evaluation of the effect of fly ash and zeolite powder and glass fiber on flexural behavior of structural lightweight beams made of Scoria - yousef zandi (Iranian Society of Structrual Engineering (ISSE), 2020)
Lowering the weight of concrete used in buildings and other structures has been one of the main priorities of the specialists. This will reduce the dead load and the forces involved in the structure during the earthquake. A wide range of research has been done around the world.In this work, a research on the construction of lightweight aggregates of Scoria has been used to increase the flexural strength of the beams tested in the glass fiber, as well as to reduce the use of cement, reduce the amount of pollutants in Iran, as well as increase the efficiency of concrete from zeolite and ash powder The wind has been used and the mechanical characteristics of these lightweight concrete structures, in particular the flexural behavior of lightweight structural beams, have been investigated in the laboratory environment, and the results indicate that light concrete was constructed and pressurized in Due to the presence of a network of fibers up to 3% by weight of cement and the resulting flexibility, the strain is very crisp And preventing it from breaking down and increasing the compressive strength by up to 20% and 10% of the flexural strength compared to the control sample. Addition of powdered zeolite along with ash to 15% by weight of cement has the same adhesion properties as cement to light concrete Data has increased the flexural strength by up to 15%.